2020
DOI: 10.1159/000516477
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Inner Ear Saccular Development in the Plainfin Midshipman (Porichthys notatus)

Abstract: The auditory system of the plainfin midshipman fish (<i>Porichthys notatus</i>) is an important sensory system used to detect and encode biologically relevant acoustic stimuli important for survival and reproduction including social acoustic signals used for intraspecific communication. Previous work showed that hair cell (HC) density in the midshipman saccule increased seasonally with reproductive state and was concurrent with enhanced auditory saccular sensitivity in both females and type I males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Linear ontogenetic increases in macular area and HCT were also documented in the saccule, lagena, and utricle of G. galeus, the only other ontogenetic study of inner ear HCs in elasmobranch otolith organs (Sauer et al, 2022). Studies on various otolith organs of bony fishes have also reported ontogenetic increases in macular area and HCT (Popper and Hoxter, 1984;Lombarte and Popper, 1994;Higgs et al, 2002Higgs et al, , 2003Chaves et al, 2017;Lozier and Sisneros, 2020). While the functional significance of these ontogenetic changes is unclear, it has been suggested that increasing HCT may enhance auditory sensitivity as fishes grow (Corwin, 1983;Coffin et al, 2012;Lu and Desmidt, 2013;Wang et al, 2015) or could act to maintain stable hearing throughout ontogeny (Popper et al, 1988;Rogers et al, 1988;Higgs et al, 2003).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Linear ontogenetic increases in macular area and HCT were also documented in the saccule, lagena, and utricle of G. galeus, the only other ontogenetic study of inner ear HCs in elasmobranch otolith organs (Sauer et al, 2022). Studies on various otolith organs of bony fishes have also reported ontogenetic increases in macular area and HCT (Popper and Hoxter, 1984;Lombarte and Popper, 1994;Higgs et al, 2002Higgs et al, , 2003Chaves et al, 2017;Lozier and Sisneros, 2020). While the functional significance of these ontogenetic changes is unclear, it has been suggested that increasing HCT may enhance auditory sensitivity as fishes grow (Corwin, 1983;Coffin et al, 2012;Lu and Desmidt, 2013;Wang et al, 2015) or could act to maintain stable hearing throughout ontogeny (Popper et al, 1988;Rogers et al, 1988;Higgs et al, 2003).…”
Section: Discussionmentioning
confidence: 95%
“…The smaller size range of C. isabellum (∼20-90 cm) compared to G. galeus (∼30-170 cm) might minimize ontogenetic changes in HCD, although Corwin (1977Corwin ( , 1981a reported no differences in HCD of the macula neglecta between juvenile and adult blacktip and gray reef sharks (Carcharhinus melanopterus and Carcharhinus amblyrhynchos, respectively), two species with similar size ranges to G. galeus. There is likely variation in HCD patterns between elasmobranchs, similar to in bony fishes, where data indicate that ontogenetic changes in HCD may be species-specific, macula-specific, and even dependent on developmental stage (Popper and Hoxter, 1984;Lombarte and Popper, 1994;Higgs et al, 2002;Lu and Desmidt, 2013;Wang et al, 2015;Chaves et al, 2017;Lozier and Sisneros, 2020). Further quantification of HCD across full size ranges and in all inner ear maculae, especially in elasmobranchs, is needed to characterize postembryonic development of HCD in fishes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations